Evaluation of the SB 1041 reforms to California's CalWORKs Program : background and study design - Karoly, Lynn A., 1961-; Bozick, Robert; Davis, Lois M.; Kitmitto, Sami; Turk-Bikakci, Lori; Bos, Johannes M.; Holod, Aleksandra; Blankenship, Charles (RAND Corporation, 2015)
The California Budget Act of 2012, also known as Senate Bill (SB) 1041, contained significant reforms to the California Work Opportunity and Responsibility to Kids (CalWORKs) program. CalWORKs, administered by the California Department of Social Services (CDSS), is California's Temporary Assistance for Needy Families (TANF) program, a central component of the safety net that provides cash aid for low-income families with children. The SB 1041 reforms to CalWORKs included changes to requirements for work, the types of eligible work activities, the time clock that governs the work requirements, and the financial incentives to work--all with goal of engaging recipients in more-intensive work activities as early as possible, while also providing more flexibility in work activity options and increased incentives for work as recipients move toward self-sufficiency. The California legislature included a provision in the bill for an independent evaluation to determine if SB 1041 achieves its objectives and if there are any unintended consequences. The purpose of this report is to provide background on the SB 1041 reforms and offer an overview of the evaluation plan. In the remainder of this summary, we first highlight the factors that motivated the changes to CalWORKs and summarize the key reforms. We then delineate the questions underlying the SB 1041 evaluation and the evaluation approach. A final section covers the evaluation timetable, products, and expected utility.